2017
DOI: 10.1002/rcm.7939
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of species classification models of mass spectrometry data: Kernel Discriminant Analysis vs Random Forest; A case study of Afrormosia (Pericopsis elata (Harms) Meeuwen)

Abstract: Rationale:The genus Pericopsis includes four species of which only Pericopsis elata (Harms) Meeuwen is of commercial interest. Enforcement officers might have difficulties discerning this CITES-listed species (Appendix II) from some other tropical African timber species. Therefore, we tested several methods to separate and identify these species rapidly in order to enable customs to uncover illegal trade. In this study, two classification methods using DART TOFMS data to discern between several species are pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…Thus, direct analysis in real time has been recently used to classify tree species. 38 Extractive electrospray ionization and secondary electrospray ionization have demonstrated some potentialities. 39,40 Ambient mass spectrometry techniques and their applications were reviewed.…”
Section: Ms-based Electronic Nose-direct Injection Msmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, direct analysis in real time has been recently used to classify tree species. 38 Extractive electrospray ionization and secondary electrospray ionization have demonstrated some potentialities. 39,40 Ambient mass spectrometry techniques and their applications were reviewed.…”
Section: Ms-based Electronic Nose-direct Injection Msmentioning
confidence: 99%
“…It is out of the scope of this article to be exhaustive, but it is worthwhile citing ambient mass spectrometry techniques that found applications in VOC profiling. Thus, direct analysis in real time has been recently used to classify tree species . Extractive electrospray ionization and secondary electrospray ionization have demonstrated some potentialities .…”
Section: Introductionmentioning
confidence: 99%
“…Chemical analysis tools, such as mass spectrometry (Fidelis et al, 2012), near-infrared spectroscopy (Braga et al, 2011;Bergo et al, 2016), and stable isotopes (Kagawa and Leavitt, 2010;Förstel et al, 2011;Vlam et al, 2018), can be used to discriminate species and verify the geographical origin of traded timber. For example, previous studies used a specific mass spectrometer to discriminate species that cannot be identified based on wood anatomy in the Americas (Espinoza et al, 2015), Africa (Deklerck et al, 2017), andAsia (McClure et al, 2015). In this study, we focus on chemical characterization by Direct Analysis in Real Time (DART) coupled with Time-of-Flight Mass Spectrometry (TOFMS).…”
Section: Introductionmentioning
confidence: 99%
“…Here we evaluate the use of DART‐TOFMS for determining the taxonomic source of keratin tissue. DART‐TOFMS has been successful in the identification of solid wood samples to determine species source . This ambient ionization technique allows for exact mass measurements of ions from a solid matrix without the need to modify or derivatize the sample.…”
Section: Introductionmentioning
confidence: 99%
“…DART-TOFMS has been successful in the identification of solid wood samples to determine species source. [21][22][23] This ambient ionization technique allows for exact mass measurements of ions from a solid matrix without the need to modify or derivatize the sample. Sample preparation is simple, requiring only a sliver of sample for analysis, which results in minimal destruction to the original item.…”
mentioning
confidence: 99%